TRENDS IN HIV PREVALENCE AND RISK BEHAVIOR AMONG MEN WHO HAVE SEX WITH MEN IN NEW YORK CITY, 2004–2011 - Reilly, Kathleen H. (AIDS Educ Prev, 2014)
This study examined trends in HIV prevalence and HIV-related risk behaviors from 2004 through 2011 among men who have sex with men (MSM) in New York City. MSM were venue-sampled, interviewed, and offered HIV testing in serial cross-sectional studies. Significant differences in overall time trends were determined using the Spearman rank correlation and logistic regression models. There were 457 (2004–2005), 550 (2008), and 510 (2011) participants in each study round. There was no significant trend in HIV prevalence over time, and past 12 month unprotected anal intercourse remained steady. However, drug use and number of sex partners declined. Among those who did not self-report being HIV positive, the percentage that tested for HIV in the past 12 months increased. The results from this study suggest that from 2004 through 2011 more MSM in New York City are being tested for HIV and have declining drug use and fewer sex partners.